The assembly rules guiding hetero-oligomeric bacterioferritin organization and their evolutionary signature - Daniel Stein; Bruno Jartoux; Shiran Dror; René Uebe; Tracy Chih-Ting Koubková-Yu; Ran Zalk; Anat Shahar; Raz Zarivach; Gabriel A. Frank (Proceedings of the National Academy of Sciences, 2026)
Homomeric and heteromeric protein complexes are ubiquitous across all domains of life. The evolutionary transition from homo- to hetero-oligomers by gene duplication and chain specialization is widespread, yet it entails challenging requirements for maintaining oligomerization and functionality. Chain specialization in ferritins, which occurs in bacteria, vertebrates, and plants, is a salient example of this phenomenon. In heteroferritins, the two essential functions, ferroxidase activity and electron transfer, are split between two specialized chain types. Many heteroferritins assemble into complexes with variable subunit ratios, implying the existence of assembly rules that balance compositional flexibility with structural constraints. Here, we identify the assembly rules governing the organization of the heterobacterioferritin from Magnetospirillum gryphiswaldense (MSR-1 Bfr) by analyzing its cryo-EM reconstructions. These rules consist of structural constraints that limit the number of possible arrangements and promote juxtaposition of the two, now separated functions. These constraints support compositional flexibility while preserving function, thereby providing resilience to stochastic variation in oligomer stoichiometry. Bioinformatic analysis revealed that the assembly rules identified in MSR-1 Bfr are widespread across the Bfr family and coevolved with chain specialization. Together, these findings support leading models of hetero-oligomer evolution and reveal the emergence of order-exerting mutations that shape the organization of multimeric protein complexes while conserving function.